Considering Seasonal Variations in Food Availability and Caring Capacity when Planning Complementary Feeding Interventions in Developing Countries - Wijesinha-Bettoni, Ramani; Kennedy, Gina; Dirorimwe, Charity; Muehlhoff, Ellen (International Journal of Child Health and Nutrition, 2013)
During early childhood, adequate nutrition is critical for preventing and reducing chronic undernutrition and micronutrient deficiencies. Seasonal food availability, access to diverse food and maternal workload are among the known constraints to successful infant and young child feeding practices. In rural areas in developing countries, many populations experience seasonal food shortages, which often coincide with an increase in food prices and a peak period for agricultural labour. Seasonal pressure on women’s time can negatively impact cooking and caring practices and intra-family food distribution. These factors combine to affect the nutritional status of especially children and women. This paper shows how seasonal food availability data are collected and utilized in designing complementary feeding interventions. Examples are drawn from FAO food and nutrition security projects in Afghanistan, Cambodia, Laos and Zambia which began with formative research using Trials of Improved Practices. Methods include use of seasonal food availability calendars and development of season-specific dishes and recipes. How seasonal variations in food availability and caring capacity feature in the educational materials developed by these projects is also reported. Finally, we provide practical ideas for incorporating coping strategies for dealing with seasonal effects when planning such interventions.